Investigation of the microorganism combinations on aroma in fermented sucuk - Yağmur Nil Demirel; Zeki Gürler (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was investigated that microorganism combinations which are obtained from natural flora of sucuk dough producing traditional method, effect on aroma. Materials and Methods: L. plantarum, L.sake, L. curvatus, S. xylosus were isolated and identified from sucuk dough and mixtured three different ways. Sucuk production was made by using these microorganism combinations in three times. Qualitative volatile compound analysis was made by GC-MS intrumental method on three samples of each sucuk group. Results: It was calculated kovats retention index, retention time, average peak area of volatile aroma compounds. The control group has 11 volatile aroma compounds. The second group which has L. plantarum, L. sake, S. xylosus has 12, the third group which has L. plantarum, L. curvatus, S. xylosus has 11, the fourth group which has L. curvatus, L. sake, S. xylosus has 11 volatile aroma compounds. Total 15 volatile aroma compounds were detected. The most abundant volatile aroma compounds are gamma terpene, o-cymene, delta- 3-carene, diallyl disulfide, cumin aldehyde in sucuk groups. There haven’t been detected any volatile compounds which are presence in control group and not presence in other sucuk groups. There have been detected alpha phellandrene, camphene, 2-methylpropanoic acid, 2-methylfuran in sucuk groups but not presence in control group. Conclusions: Turkey specific microorganisms which are obtained from natural flora of sucuk dough should be used as starter culture. Then, it is investigated effective on development of sucuk aroma.